Transperitoneal laparoscopic heminephroureterectomy in the pediatric population: A single-centre experience using a sealing device - Aydogdu, Ibrahim; AYDOĞDU, İBRAHİM; SILAY, MESRUR SELÇUK (My University, 2018)
Introduction: We sought to report the outcomes of transperitoneal laparoscopic heminephroureterectomy (LHNU) in a pediatric population and to describe the technical details of this minimally invasive surgery.